Free trade zones and their economic effects - Tawfiq Abbas Abd Aoun (Iraqi Journal for Administrative Sciences, 2024)
Recently, there has been a lot of interest in free zones, which are considered centers of attraction for foreign investments, as well as their ability to create forward and backward links within the national economy and to address crises that can occur within the economy, especially the problem of unemployment, by providing additional job opportunities for the unemployed, thus increasing income and enhancing the competitiveness of goods. Local trends in foreign goods, as well as enhancing the positive balance of payments and providing foreign currencies to achieve the economic development process in the country according to economic foundations that serve the country. Research problem: Free economic zones, including the Arab region, face several obstacles and obstacles represented by the inability to activate their role within the national economy. Importance of research: Free zones have positive and negative effects that can arise through the establishment of these zones. Research objective: - Identifying the concept of free zones, the obstacles they face, the economic effects resulting from their establishment, and presenting specific proposals for the purpose of reducing their negative effects. Research hypothesis: Free zones can contribute to strengthening the national economy by attracting foreign investments when they are established according to sound economic foundations.